Microstructural and Electrochemical Analysis of the Physically Simulated Heat-Affected Zone of Super-Duplex Stainless Steel UNS S32750 - Francisco Magalhães dos Santos; Leonardo Oliveira Passos da Silva; Ygor Tadeu Bispo dos Santos; Bruna Callegari; Tiago Nunes Lima; Rodrigo Santiago Coelho (Metals)
Super-duplex stainless steels (SDSSs) were introduced in the oil and gas industry due to their high resistance to pitting corrosion, promoted by the high content of alloying elements. The welding process can cause an unbalanced ferrite/austenite microstructure and, consequently, the possibility of deleterious phases, increasing the risk of failure. The aim of this work is to investigate the behavior of the heat-affected zone (HAZ) of SDSS UNS S32750 steel produced with different thermal inputs simulated in a Gleeble® welding simulator and correlate these findings with its corrosion properties. The pitting resistance was investigated by electrochemical techniques in sodium chloride solution, and the critical pitting temperature (CPT) was calculated for each evaluated microstructure. The material as received presents 46.19 vol% ferrite and a high corrosion resistance, with a CPT of 71.54 °C. HAZ-simulated cycles resulted in similar ferrite percentages, between 54.09 vol% and 57.25 vol%. A relationship was found between heat input, ferrite content, and CPT: increasing the heat input results in greater ferrite content and lowers the CPT, which may favor the pitting corrosion process. Therefore, it is concluded that the ferrite content directly influences the pitting behavior of the material.